The Dynamics of Culture Shock and Identity Negotiation among Migrant Students at IAIN Langsa - Anjeni, Sri; Zulkarnain, Zulkarnain; Siregar, Mawardi (Al-Hikmah Media Dakwah, Komunikasi, Sosial dan Kebudayaan, 2025)
Moving to a new environment with a different cultural background often leads to the phenomenon of culture shock, particularly among migrant students who leave their hometowns to pursue higher education. Students from outside Aceh who study at IAIN Langsa face adaptation challenges within a social and cultural environment strongly influenced by Islamic law and local traditions. The mismatch between their initial expectations and the realities they encounter often triggers psychological and social reactions such as confusion, stress, and social isolation. This study aims to explore the dynamics of culture shock and the process of identity negotiation experienced by migrant students during their adaptation to the academic and social environment at IAIN Langsa. Using a qualitative approach with a phenomenological method, the study focuses on understanding the participants’ subjective experiences, with data collected through in-depth interviews involving eight purposively selected migrant students. The findings reveal that common forms of culture shock include differences in language, food, dress codes, and social interaction patterns shaped by strong religious norms. Over time, students overcome these challenges through identity negotiation by adjusting their appearance, communication style, and social behavior while constructing hybrid identities through maintaining relationships within fellow migrant communities, building cross-cultural friendships, and reinforcing their Islamic values as a means of integration. The study highlights the importance of institutional support for migrant students in their process of cultural adaptation and emphasizes the need for intercultural engagement programs on campus to foster a more inclusive and harmonious academic environment.